Third-Stream Orientalism: J. N. Farquhar, the Indian YMCA's Literature Department, and the Representation of South Asian Cultures and Religions (ca. 1910–1940). Issue 3 (August 2020) - Fischer-Tiné, Harald
Abstract : This article reconstructs the history of the Indian YMCA's Orientalist knowledge production in an attempt to capture a significant, if forgotten, transitional moment in the production and dissemination of scholarship on the religions and cultures of the Indian subcontinent. The YMCA's three Orientalist book series examined here flourished from the 1910s to the 1930s and represent a kind of third-stream approach to the study of South Asia. Inspired by the Christian fulfillment theory, "Y Orientalism" was at pains to differentiate itself from older polemical missionary writings. It also distanced itself from the popular "spiritual Orientalism" advocated by the Theosophical Society and from the philologically inclined "academic Orientalism" pursued in the Sanskrit departments of Western universities. The interest of the series' authors in the region's present and the multifarious facets of its "little traditions, " living languages, arts, and cultures, as well as their privileging of knowledge that was generated "in the field" rather than in distant Western libraries, was unusual. Arguably, it anticipated important elements of the "area studies" approach to the Indian subcontinent that became dominant in Anglophone academia after the Second World War.